Theoretical Approaches to Determining of the Definition «Social Infrastructure» as an Important Component of the Social Sphere. (Economics and region, 2017)
UDC 338.49 Oleh Zhuk, Postgraduate Student. Ivan Franko Lviv National University. Theoretical Approaches to Determining of the Definition «Social Infrastructure» as an Important Component of the Social Sphere. Theoretical approaches to determining definitions of «social infrastructure» and «social sphere» are systematized in the article. The author proposed his own interpretation of the studied categories. The structure of social sphere in which priority among components is provided by social infrastructure (there is serving as the material and technical basis) is submitted. Keywords: theoretical approaches, social sphere, social infrastructure, service industries.